Some experiences related to innovation methodologies within the university classroom - Beatriz Amante García; María Martínez Martínez (OmniaScience, 2012)
In this second year of our Journal JOTSE our main challenge is to publish experiences related to innovation methodologies within the university classroom. Thus, allowing for the implementation and/or evaluation of competences throughout students' learning process and, especially, in the scientific and technological fields. We understand competences as the combination of knowledge, skills and attitudes necessary to perform a task efficiently. Thereby, demonstrating abilities in action and developing them through activities that integrate all these aspects. In the area of higher studies in the scientific and/or technological fields it is rather common that the methodologies developed have a very practical component and, in addition, they are closely linked to the professional career our students are being trained for. Particularly, in the last academic years and at the end of their studies it is when students attend more applied subjects, such as Projects in the case of Engineering Studies that together with the Degree's Final Project (PFC) allow to integrate a wide range of generic or cross-curricular competences and specific ones within the field. These types of subjects have shown to be very efficient to make students become closer to the professional reality that they will face at the end of their studies and where they will have to provide a solution for problematic situations or to meet the needs nowadays society demands. (Dochy et al. (2003), Prince (2004),Prince and Felder (2006)) Furthermore, with the incorporation to Bologna process, targeting a more active role of students during their learning process, it is even more relevant that students face real problems from the very beginning of their studies so that they gradually acquire generic competences, which are vital for their training both as individuals and as professionals in our present society. It is within this context that Problem-Based Learning (PBL) has proved its usefulness to reach such an objective. In this sense, several authors have shown that PBL can be successfully implemented in Engineering studies and as early as in the first year (Del Canto, 2011) by integrating teamwork among other competences.